Linkage Between the Siberian Storm Track and the Winter Precipitation in China - Minghao Yang; Weikai Lu; Chaohui Chen; Yongqiang Jiang; Xiong Chen (Atmospheric Science Letters)
ABSTRACT The most active synoptic‐scale disturbances in Eurasia are embedded within the Siberian storm track. This paper investigates the linkage between the winter Siberian storm track (WSST) and the winter precipitation in China and explores the underlying physical processes. The results show that an intensified WSST is associated with a decrease in winter precipitation along the southeast coast of China and in the East China Sea on the interannual scale. The anomalous low‐level northerly winds over eastern China and upper‐level positive vorticity anomalies over the East China Sea, accompanied by the subsidence, exert an inhibitory effect on precipitation. The anomalous moisture flux divergence related to northerly winds reduces the moisture supply. The interaction between WSST and mean flow may sustain the anomalous large‐scale atmospheric circulation and baroclinicity. In addition, synoptic‐scale disturbances originating from the WSST region propagate to the East China Sea, forming cyclonic circulation anomalies that are unfavorable for precipitation.